2018
DOI: 10.3991/ijet.v13i02.8031
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Academic Performance of Students in Blended and Traditional Domains

Abstract: Abstract-This paper aims to identify the most important and significant factors in two different areas of learning: combined and traditional learning. Several critical issues have not yet been resolved to achieve the full potential of the learning outcomes in the two domains. The objective of this paper is to review the critical factors that have a great influence on academic performance. The document focuses specifically on a set of factors such as the use of technology, the interaction processes, the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Findings from prior studies Edward et al (2018); Ghazal et al (2018) indicated that BL approach enhances students' learning engagement and experience as it creates a significant influence on students' awareness of the teaching mode and learning background. BL moves the emphasis from teaching to learning, thus enabling students to become more involved in the learning process and more enthused and, consequently, improves their perseverance and commitment (Ismail et al 2018a). Poon (2014) concluded that BL is likely to be developed as the leading teaching approach for the future as one of the top ten educational trends to occur in the twentyfirst century.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from prior studies Edward et al (2018); Ghazal et al (2018) indicated that BL approach enhances students' learning engagement and experience as it creates a significant influence on students' awareness of the teaching mode and learning background. BL moves the emphasis from teaching to learning, thus enabling students to become more involved in the learning process and more enthused and, consequently, improves their perseverance and commitment (Ismail et al 2018a). Poon (2014) concluded that BL is likely to be developed as the leading teaching approach for the future as one of the top ten educational trends to occur in the twentyfirst century.…”
Section: Introductionmentioning
confidence: 99%
“…Student academic success is strongly influenced by internal and external factors (Hamid, 2019). The influence of internal factors such as student characteristics and personality is International Journal of Instruction, April 2021 • Vol.14, No.2 important determinants in predicting students' academic performance in the classroom (Ismail, Mahmood, and Abdelmaboud, 2018). Ciorbea and Pasarica (2013), stated that personality factors are variables that influence student academic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Global and local studies have identified myriad factors which influence students' academic achievement such as family factors, teacher factors, students' attitudes, use of technology, interaction processes, characteristics of the students, and class among others [3][4][5][6]. However, poor performance has persisted necessitating the study of other variables that might account for the students' academic achievement.…”
Section: Introductionmentioning
confidence: 99%